The labour market of young graduates in Portugal: The effect of higher education reform and economic recession - Figueiredo, M. C. T.; Suleman, F. (SRHE International Conference on Research into Higher Education, 2018)
This paper examines determinants of the wages of young under and master graduates engaged in different contractual arrangements in Portugal. Linked employer-employee data, namely Quadros de Pessoal (2007 and 2011), was used to compare the impact of flexibility (stability), part-time (full-time) and occasional jobs on wages of post-Bologna graduates who entered in the labour market during the economic recession. Most graduates start by getting a full-time job, be it stable or flexible. Empirical evidence shows wage differentials among the five types of arrangement, although the impact varies between 2007 and 2011. The contracts that combine flexibility with part-time work have been the most penalised in recent times. Whereas the transition of undergraduates to the labour market is expected to be more precarious, post-graduates appear to be protected against low quality jobs in Portugal. The findings show that it is increasingly difficult for young graduates to access high quality jobs.